(untitled) (Colombia Medica, 2016)
Abstract Objective: To assess the self-reported vaccination in older adults within the city of Bogotá and its distribution by sociodemographic factors. Methods: Data analyzed was taken from the SABE-Bogotá study. A total of 2000 persons aged 60 years and older were selected for this cross-sectional population-based study. Bivariate and multivariate analyses were performed testing the association between vaccination and sociodemographic factors. Results: A total of 73.0% of respondents received the influenza vaccine, 57.8% received pneumococcal vaccine and 47.6% received tetanus vaccine. In multivariate analyses, individuals aged between 65-74 years had higher odds of receiving influenza, pneumococcus and tetanus vaccination, compared to those between 60-64 years. Older adults with higher socioeconomic status (SES) had lower odds of having influenza and pneumococcus vaccines, compared to those with lower SES (OR= 0.16 95% confidence intervals= CI 0.08-0.30; OR 0.20 95% CI 0.10-0.38, respectively). Individuals covered by health insurance (contributive or subsidized) had higher odds (between 3 and 5 times higher) of having influenza, pneumococcus and tetanus vaccination, compared to those with no insurance. Conclusion: Older adults between 65 and 74 years, those with health care coverage and people with low SES are groups that have increased odds for self-reported vaccination. Further studies should identify factors that increase vaccination coverage in these groups and implement interventions targeted at improving coverage among older adults in general.